PATHS OF INCOME CONVERGENCE BETWEEN COUNTRY PAIRS WITHIN EUROPE - Gligoric, Mirjana (Economic Annals, 2014)
This paper explores income convergence in European countries. Unlike previous research, the analysis is based on the pair-wise approach (Pesaran, 2007), identifying four cases: long-run convergence, catching-up, lagging-behind, and divergence. The results suggest that catching-up prevails, while no significant evidence was found for the existence of long-run convergence at the whole sample level. Still, three convergence clubs appear that consist of countries recording long-run convergence, two in transitional countries and one involving advanced countries, which indicate the similar growth model of the countries belonging to each club. Nevertheless, the results do not allow us to claim with certainty that the income paths of the club members will not exhibit systematic tendencies toward divergence or changes in membership in future.